2006
DOI: 10.1002/elps.200500640
|View full text |Cite
|
Sign up to set email alerts
|

Counterion‐dye staining for DNA in electrophoresed gels using indoine blue and methyl orange

Abstract: In this study, we describe a sensitive staining method for DNA in agarose and polyacrylamide gels using organic visible dyes, indoine blue (IB) and methyl orange (MO). The counterion-dye staining method uses two oppositely charged dyes to form a hydrophobic ion pair complex in the staining solution. A decrease in the number of free forms of dyes in staining solution can enhance the selectivity of binding between the dye and DNA, and can reduce nonspecific background staining. As a result, the sensitivity of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This was confirmed by our own result from methylene blue staining (data not shown). More recently, Choi et al developed the counterion−dye staining method, , which showed low background staining and hence improved sensitivity. We tried this method, but the sensitivity was poor in our hands, possibly because this method is not compatible with SDS−PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…This was confirmed by our own result from methylene blue staining (data not shown). More recently, Choi et al developed the counterion−dye staining method, , which showed low background staining and hence improved sensitivity. We tried this method, but the sensitivity was poor in our hands, possibly because this method is not compatible with SDS−PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…For example, interactions with human serum albumin have been reported (Ito & Yamamoto, 2015). To our knowledge, methyl orange alone does not interact with DNA; however, when used in combination with other dyes like crystal violet or indoine blue, the resulting complexes are able to interact with DNA (Hwang, Jin, Yoo, & Choi, 2006;Yang, Jung, Bai, Yoo, & Choi, 2001). In such delicate conditions, another method for CMC determination should be considered.…”
Section: Troubleshootingmentioning
confidence: 99%
“…Current Protocols in Protein Science combination with other dyes like crystal violet or indoine blue, the resulting complexes are able to interact with DNA (Hwang, Jin, Yoo, & Choi, 2006;Yang, Jung, Bai, Yoo, & Choi, 2001). In such delicate conditions, another method for CMC determination should be considered.…”
Section: Of 27mentioning
confidence: 99%
“…In addition, mercury can affect human body organs through binding to the thiol groups of amino acids and proteins, thereby causing serious damage to the central nervous system, brain, kidney, and respiratory system. [14][15][16][17][18][19] The US Environmental Protection Agency (EPA) and the World Health Organization (WHO) have set the maximum allowed concentration of Hg 2+ in drinking water at 2 ppb (10 nM). 20 The determination of Hg 2+ pollution in environment is usually carried out by conventional advanced methods such as inductively coupled plasma mass spectroscopy (ICP-MS), 21 atomic absorption spectroscopy (AAS), 22 high performance liquid chromatography (HPLC), 23 and inductively coupled plasma-atomic emission spectrometry (ICP-AES).…”
Section: Introductionmentioning
confidence: 99%